ISLAMIC FINANCIAL AWARENESS AND SUSTAINABLE FINANCIAL BEHAVIOR OF GENERATION Z - Zulfatun Anisah (PAPUA: International Journal of Sharia Business Management, 2026)
This study examines the role of Islamic Financial Awareness in fostering Sustainable Financial Behavior among Generation Z in Indonesia. The rapid growth of Islamic financial services, digital financial platforms, and financial technology has increased opportunities for young consumers to access financial products and services. However, concerns remain regarding the limited level of Islamic financial awareness and the increasing prevalence of consumptive financial behavior among Generation Z. This study employs a quantitative approach with an explanatory research design to analyze the relationship between Islamic financial awareness and sustainable financial behavior. Islamic Financial Awareness is conceptualized through knowledge of Sharia principles, Islamic financial products, and ethical financial values, while Sustainable Financial Behavior is reflected in budgeting, saving, responsible spending, debt management, and long-term financial planning. The findings indicate that a higher level of Islamic financial awareness contributes positively to the development of sustainable financial behavior by encouraging responsible financial decision-making and strengthening financial resilience. The study highlights the importance of enhancing Islamic financial education and awareness programs to support the formation of a financially responsible and sustainable Generation Z in Indonesia.